THERapy–Related InterACTion (THER-I-ACT) in Rehabilitation—Instrument Development and Inter-Rater Reliability - Platz, Thomas; Seidel, Jonathan; Müller, Andreas; Goldmann, Carolin; Pedersen, Ann Louise (Frontiers in Neurology, 2021)
Objective: To develop an instrument for the observation of therapeutic communication interactions during rehabilitation sessions and test its inter-rater reliability. Methods: The new instrument THER-I-ACT (THERapy–related Inter-ACTion) has been designed to assess both the frequency and timing of therapeutic interactions in the thematic fields information provision, feedback, other motivational interaction, and bonding. For this inter-rater reliability study, a sample of stroke survivors received arm rehabilitation as either arm ability training, arm basis training, or mirror therapy, or neglect training as individually indicated. Therapy sessions were video-recorded (one for each participant) and therapeutic interactions rated by two independent raters using THER-I-ACT. Results: With regard to the instrument's comprehensiveness to document therapeutic interactions with pre-defined categories the data from 29 sessions suggested almost complete coverage. Inter-rater reliability was very high both for individual categories of therapeutic interaction (frequency and time used for interaction) (intraclass correlation coefficient, ICC 0.91–1.00) and summary scores for the thematic fields of interaction (again for frequency and time used for interaction) (ICC 0.98–1.00). The inter-rater reliability for rating engagement and being focussed for both the therapist and patient was substantial (ICC 0.71 and 0.86). Conclusions: The observational study documented that by use of the newly designed THER-I-ACT various types of therapy-related communication interactions performed by therapists can be assessed with a very high inter-rater reliability. In addition, the thematic fields and categories of therapeutic interaction as defined by the instrument comprehensively covered the type of interaction that occurred in the therapeutic sessions observed.